Play it again: Partner choice, reputation building and learning in restarting, finitely-repeated dilemma games - Kenju Kamei; Louis Putterman (Brown University, Department of Economics, 2013)
Previous research has shown that opportunities for two-sided partner choice in finitely repeated social dilemma games can promote cooperation through a combination of sorting and opportunistic signaling, with late period defections by selfish players causing an end-game decline. How such experience would affect play of subsequent finitely-repeated games remains unclear. In each of six treatments that vary the cooperation premium and the informational basis for reputation formation, we let sets of subjects play sequences of finitely-repeated voluntary contribution games to study the competing forces of (a) learning about the benefits of reputation, and (b) learning about backward unraveling. We find, inter alia, that with a high cooperation premium and good information, investment in reputation grows across sets of finitely-repeated games.
Keywords: C92; D74; D83; H41; 330; cooperation; reputation; voluntary contribution; public goods; sorting; endogenous grouping; group formation; experiment